Housing Policy in India - priti (Innovative Research Thoughts, 2017)
In this paper we critique the Government of India's programmes for affordable housing in India, namely the Rajiv Awas Yojana and Housing for All 2022. We analyse the efficacy of these policies in being able to provide thee sections of the population who are unable to avail housing from the formal market, both through direct support and most importantly in addressing the many distortions that have made the housing unnecessarily expensive, while taking away much of the value to consumers. We argue that while these programmes and policies are a major advancement over the previous approaches, they do not fully exploit the potential that is there in increased FSI, sensitivity of low cost housing development to exploiting location value appropriately, to use of government land judiciously, to the reform of titles and squatter rights, and to more efficient land use changes. They are also constrained by an inability to distinguish between what the markets can be coaxed to deliver and where state intervention becomes necessary